Identification of Host Bloodmeal Source in Ornithodoros turicata Dugès (Ixodida: Argasidae) Using DNA-Based and Stable Isotope-Based Techniques - Kim, Hee J.; Hamer, Gabriel L.; Hamer, Sarah A.; Lopez, Job E.; Teel, Pete D. (Frontiers in Veterinary Science, 2021)
The ecology and host-feeding patterns of many soft ticks (Ixodida: Argasidae) remains poorly understood. To address soft tick-host feeding associations, we fed Ornithodoros turicata Dugès on multiple host species and evaluated quantitative PCR (qPCR) and stable isotope analysis to identify the vertebrate species used for the blood meal. The results showed that a qPCR with host-specific probes for the cytochrome b gene successfully identified blood meals from chicken (Gallus gallus L.), goat (Capra aegagrus hircus L), and swine (Sus scrofa domesticus) beyond 330 days post-feeding and through multiple moltings. Also, qPCR-based bloodmeal analyses could detect multiple host species within individual ticks that fed upon more than one species. The stable isotope bloodmeal analyses were based on variation in the natural abundance of carbon (13C/12C) and nitrogen (15N/14N) isotopes in ticks fed on different hosts. When compared to reference isotope signatures, this method discerned unique δ13C and δ15N signatures in the ticks fed on each host taxa, yet could not discern multiple host species from O. turicata that fed on more than one host species. Given the significance of soft tick-borne zoonoses and animal diseases, elucidating host feeding patterns from field-collected ticks using these methods may provide insight for an ecological basis to disease management.